Global value chains and the CPTPP - CHANG, Pao-Li (Institutional Knowledge at Singapore Management University, 2019)
The CPTPP, or the Comprehensive and Progressive Agreement for Trans-Paciﬁc Partnership, is an example of a “mega-regional” free trade agreement, whose provisions on the rules of origin and trade facilitation can have potentially large impacts on the CPTPP-wide supply chains. In this paper, we investigate whether the CPTPP members are key upstream and downstream trade partners to each other in the global value chains. We develop formulas of bilateral upstreamness and downstreamness, based on the gross-export decomposition framework of Koopman, Wang and Wei (2014) and Borin and Mancini (2017). We demonstrate how the decomposition of gross exports can be used to construct informative measures of the position of countries in global value chains.